2014
DOI: 10.1039/c3dt53323a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structure and EPR spectroscopic analysis of novel copper complexes formed from N-pyridyl-4-nitro-1,8-naphthalimide ligands

Abstract: The mono-dentate, pyridyl containing, nitro naphthalimide ligands N-(4-pyridyl)-4-nitro-1,8-naphthalimide (L 1 ) and N-(3-pyridyl)-4-nitro-1,8-naphthalimide (L 2 ) were prepared and complexed with a selection of copper salts [Cu(OAc) 2 , Cu(CF 3 SO 3 ) 2 and Cu(ClO 4 ) 2 ]. Crystallographic studies were undertaken and revealed that dinuclear acetate bridged complexes resulted from reactions with Cu(OAc) 2 , while mononuclear systems resulted from reactions with Cu(CF 3 SO 3 ) 2 and Cu(ClO 4 ) 2 . Despite the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…The spectra consist of a strong band centered around g =1.44 with two additional weak bands. These spectra closely match the EPR spectra of antiferromagnetically coupled dicopper(II)‐tetracarboxylate complexes reported earlier in the literature …”
Section: Resultssupporting
confidence: 89%
“…The spectra consist of a strong band centered around g =1.44 with two additional weak bands. These spectra closely match the EPR spectra of antiferromagnetically coupled dicopper(II)‐tetracarboxylate complexes reported earlier in the literature …”
Section: Resultssupporting
confidence: 89%
“…The non‐bridging carboxylate adopts a bonding mode from a clearly asymmetric chelating to monodentate. The Cu(2)‐N bond lengths are also in good agreement with the values reported for similar compounds …”
Section: Resultssupporting
confidence: 88%
“…In line with our previous studies [35] our primary aim was to probe the ability of L 1 and L 2 to develop higher order supramolecular architectures in combination with metal salts and here we have employed Cu(II) for this purpose.. In doing so we have shown that these simple ligands generate systems where structure extension occurs through π···π and anion···π interactions.…”
Section: Introductionmentioning
confidence: 65%
“…The Cu(II) ions are 2.651(2) Å apart, similar to other copper paddlewheel complexes. [35] The copper ions are adopt a near perfect square-based pyramidal geometry with the degree of trigonality (τ) being 0. [43] Bond lengths and angles are also consistent with other axially elongated square-based pyramidal structures where the equatorial acetate oxygen Cu-O bond lengths average 1.968(2) Å whilst the axial triazole nitrogen atom Cu-N bond length is 2.180(2) Å (Table 2).…”
Section: Crystallographic Analysis Of [Cu 2 (L 1 ) 2 (Oac) 4 ]mentioning
confidence: 99%